Associations of Workplace Violence With Cardiovascular Disease Among United States Workers: Findings From a National Survey - Zheyu Hu; Jian Li (Journal of Preventive Medicine and Public Health, 2023)
Objectives Recent research indicates a potential association between workplace violence and an increased risk of cardiovascular disease (CVD) in the working-age population. However, the relevant evidence in the United States is sparse. Thus, this study was conducted to explore the possible relationship between workplace violence and CVD among United States workers. Methods We utilized cross-sectional data from the 2015 National Health Interview Survey, which included a representative sample of 18 380 workers, to investigate the associations between workplace violence and the prevalence of CVD using logistic regression. Workplace violence was determined based on self-reported threats, bullying, or harassment at work over the past 12 months, supplemented with additional information regarding frequency. CVD included all forms of heart disease and stroke. Results A total of 1334 workers reported experiences of workplace violence, and 1336 workers were diagnosed with CVD. After adjustment for covariates, participants who reported any instance of workplace violence had significantly higher odds of having CVD (odds ratio [OR], 1.76; 95% confidence interval [CI], 1.35 to 2.30) than those who reported no such violence. Furthermore, the highest odds of CVD (OR, 1.80; 95% CI, 1.23 to 2.63) were observed among those frequently exposed to workplace violence. Even occasional exposure to workplace violence was associated with 74% excess odds of CVD. Conclusions Our study indicates an association between workplace violence and CVD in United States workers, exhibiting a dose-response pattern.